2009
DOI: 10.1002/eji.200839149
|View full text |Cite
|
Sign up to set email alerts
|

Oncostatin M deficiency leads to thymic hypoplasia, accumulation of apoptotic thymocytes and glomerulonephritis

Abstract: Oncostatin M (OSM) has been implicated in immune regulation, though its precise role remains elusive. Here we show that OSM plays a crucial role in the prevention of autoimmune diseases. OSM-deficient mice showed normal development of T cells, B cells and DC; however, their thymus showed hypoplasia and altered medullary structure. Autoantibodies against dsDNA accumulated and glomerulonephritis developed in aged OSMdeficient mice. Apoptotic cells accumulated in the thymus of OSM-deficient mice, and the administ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 27 publications
1
19
0
Order By: Relevance
“…We linked this reduction in neuronal OSMR␤ to neuronal death, at least in response to I/R, using TUNEL and Fluoro-Jade B staining in vivo and cell viability assays in vitro. These findings were supported by a previous study by Esashi et al (2009), who reported that OSM deficiency enhanced thymocyte apoptosis. Moreover, keratinocytes carrying mutated OSMR␤ appeared to be more susceptible to apoptosis, resulting in cell death and the accumulation of degenerated keratinous material in the superficial dermis .…”
Section: Discussionsupporting
confidence: 89%
“…We linked this reduction in neuronal OSMR␤ to neuronal death, at least in response to I/R, using TUNEL and Fluoro-Jade B staining in vivo and cell viability assays in vitro. These findings were supported by a previous study by Esashi et al (2009), who reported that OSM deficiency enhanced thymocyte apoptosis. Moreover, keratinocytes carrying mutated OSMR␤ appeared to be more susceptible to apoptosis, resulting in cell death and the accumulation of degenerated keratinous material in the superficial dermis .…”
Section: Discussionsupporting
confidence: 89%
“…Other gp130-related cytokines may, however, govern defined aspects of pathology, as is illustrated by the role of IL-11 and OSM in bone turnover (42). Indeed, OSMRβ-KO mice exhibit impaired hepatocyte proliferation (43) and altered monocytic cell trafficking (44), while OSM deficiency is associated with thymic hyperplasia and glomerulonephritis (45). Despite these apparent roles for other gp130-related cytokines in autoimmunity, therapies that target IL-6 or its receptor remain the most developed strategies.…”
Section: Figurementioning
confidence: 99%
“…Mice deficient for OSM (OSM-KO) and OSM receptor β chain (OSMRβ-KO) were previously described [43,44] and obtained from Pr. A. Miyajima…”
Section: Animalsmentioning
confidence: 99%
“…Mice deficient for OSM (OSM-KO) and OSM receptor β chain (OSMRβ-KO) were previously described [43,44] and obtained from Pr. A. Miyajima (Laboratory of Cell Growth and Differentiation, Institute of Molecular and Cellular Biosciences, The University of Tokyo, Japan).…”
Section: Animalsmentioning
confidence: 99%